A Framework to Calculate Annual Landscape Ecological Risk Index Based on Land Use/Land Cover Changes: A Case Study on Shengjin Lake Wetland - Penghai Wu (IEEE, 2021)
Wetlands are highly productive ecosystems that provide functions and services important for human survival and development. Long-term wetland landscape ecological risk assessments (LERAs) are able to effectively identify key elements for landscape sustainability; however, previous calculations of landscape ecological risk index (LERI) have only used an image each year. An individual LERI may introduce considerable uncertainties for long-term monitoring and spatio-temporal evolution when landscape types have significant seasonal differences. This article used Shengjin Lake wetland as a case study to propose a framework to calculate the annual LERI based on land use/land cover (LULC) data. The spatio-temporal evolution of annual LERA was then investigated over four periods from 1989 to 2019; there were three key findings from the analysis. First, the LULC types in Shengjin Lake wetland changed in time and space, particularly for water bodies, reed beach, and mudflats. Second, the individual LERI may only reflect ecological risks in a unique time or a season; however, they cannot represent ecological risks during the other seasons or over an entire year. Third, the annual LERI can fully reflect the landscape ecological risk at the annual scale, showing that the risk for Shengjin Lake initially rises, and then slows down over the last 30 years. In brief, the framework constructed in this study may be widely applicable, offering a reference for the monitoring, assessment, and management of other wetlands.